Immobilized copper(II) on nitrogen‐rich polymer‐entrapped Fe3O4 nanoparticles: a highly loaded and magnetically recoverable catalyst for aqueous click chemistry. (25th November 2015) - Zohreh, Nasrin; Hosseini, Seyed Hassan; Pourjavadi, Ali; Bennett, Craig
Abstract : A heterogeneous magnetic copper catalyst was prepared via anchoring of copper sulfate onto multi‐layered poly(2‐dimethylaminoethyl acrylamide)‐coated magnetic nanoparticles and was characterized using various techniques. The catalyst was found to be active, effective and selective for one‐pot three‐component reaction of alkyl halide, sodium azide and alkyne, known as copper‐catalyzed click synthesis of 1, 2, 3‐triazoles. As little as 0.3 mol% of catalyst was found to be effective under the optimum conditions. The catalyst could also be recycled and reused up to seven times without significant loss of activity.Thermal stability, high loading level of copper on catalyst, broad diversity of alkyl/benzyl/allyl bromide/chloride and alkyl/aryl terminal alkynes without isolation of azideintermediate, and good to excellent yields of products make this procedure highly economical. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A heterogeneous magnetic copper catalyst was prepared via anchoring of copper sulfate onto multilayered poly(2‐dimethylaminoethyl acrylamide)‐coated magnetic nanoparticles (MNP@PDMA‐Cu). The catalyst was found to be active, effective and selective for one‐pot three‐component reaction of alkyl halide, sodium azide and alkyne, known as copper‐catalyzed click synthesis of 1, 2, 3‐triazoles. As little as 0.3 mol% of catalyst was found to be effective under optimum conditions.